Implementation of Black Box Testing with the Application of Equivalence Partitioning Techniques in the M-Magazine Android Application at Semen Gresik High School - Frayudha, Angga Debby; Pande, Ivan Roy; Juwita, Mario Benson (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2024)
This research aimed to improve the M-Magazine application at Semen Gresik High School to enhance its usability for students and teachers. The study focused on developing a digital platform called